Understanding the impact of soil microbiome on strawberry growth and nutritional profiles - Kwak, Min-Jin; Pandey, Sriniwas; Zhai, Yuting; Choi, Bugil; Sutthanonkul, Thanyachanok; Lee, Won Suk; Jeong, Kwangcheol C. (Frontiers in Microbiology, 2025)
The rhizosphere microbiome plays an important role in plant growth, nutrient acquisition, and overall health. In this study, we investigated the relationship between the rhizosphere microbiome and the health status of strawberries (Fragaria × ananassa) under identical soil and environmental conditions. Strawberry plants were categorized into a healthy group (H) and an unhealthy group (UH) based on morphological characteristics, and the soil microbial community was analyzed using 16S rRNA gene sequencing. The H group exhibited significantly higher nitrogen concentrations, whereas the UH group showed excessive accumulation of iron, manganese, zinc, and copper. Microbiota analysis revealed distinct structural differences between the H and UH groups, with several bacterial taxa displaying significant differences in relative abundance. Notably, Microvirga and JG30-KF-CM45 emerged as key bacterial taxa associated with plant nutrient status. Microvirga was positively correlated with nitrogen levels but negatively associated with micronutrient accumulation, while JG30-KF-CM45 showed the opposite trend. Furthermore, co-occurrence network analysis indicated that microbial communities in the UH group were characterized by intensified competitive interactions, which may contribute to rhizosphere microbiome destabilization and impaired plant growth. These findings indicate that microbial interactions within the rhizosphere influence nutrient homeostasis and plant health. The observed microbial imbalances in UH plants suggest the importance of maintaining a stable microbial community for improved crop productivity. This study provides valuable insights into the role of rhizosphere microbiome in sustainable strawberry cultivation and underscores the potential of microbiome-based strategies to improve plant health and productivity.